Excavation of Later Prehistoric and Roman Sites along the Route of the Newquay Strategic Road Corridor, Cornwall - Jones, Andy M. (Archaeopress archaeology., 2019)
This volume presents the results of archaeological investigations on the Newquay Strategic Road and goes on to discuss the complexity of the archaeology, review the evidence for 'special' deposits and explore evidence for the deliberate closure of buildings especially in later prehistoric and Roman period Cornwall.